Enhancing Chemical Transportation Safety and Intelligent Control through an IoT-based Smart High-Speed Framework and Ant Algorithm Optimization - Jin, Xing; Chen, Wangzi; Yang, Jie; Sharma, Anaya (Journal of Computer Science and Software Applications, 2022)
To address the challenges of chemical transportation safety and intelligent control, a smart high-speed solution based on an IoT intelligent control platform is proposed. The overall framework is structured as '1+1+4'. The ant algorithm is integrated within this framework, enabling the optimization of transportation routes through parameter control of the ant colony algorithm. This optimization disperses risks across complex large and medium-sized road networks with multiple paths and nodes. The effectiveness of the proposed algorithm has been validated through simulation experiments and the analysis of actual operational data.